Transformation of Music Structure and Form in Marriage Ceremony of Simalungun Community in Jakarta - Purba, Hebert Lasrohadin (Universitas Negeri Surabaya, 2024)
This paper is a study of the transformation of the structure and form of music in the marriage ceremony of the Simalungun community in Jakarta. With changes in the way of working and dynamic cultural thinking, the Simalungun community in Jakarta